Analisis Persepsi Calon Mahasiswa terhadap Universitas Sanata Dharma (International Forum of Researchers and Lecturers, 2024)
Research objectives: 1) to identify and analyze the reasons influencing prospective students' interest or lack of interest in studying at Universitas Sanata Dharma, 2) to determine the study programs chosen by prospective students interested in USD, 3) to ascertain the sources of information prospective students use to learn about Universitas Sanata Dharma. This research employs a mixed methods approach with a convergent mixed methods design. Data collection was conducted through surveys (questionnaires). The research findings are as follows: 1) the reasons that influence prospective students to be interested in continuing their studies at Universitas Sanata Dharma are quality and reputation, facilities and environment, personal motivation, andUniversitas Sanata Dharma being an alternative or second choice; 2) the reasons that influence prospective students not to be interested in continuing their studies at Universitas Sanata Dharma are the university's identity, quality and reputation, cost, and personal motivation; 3) the most preferred study programs by prospective students at Universitas Sanata Dharma are Psychology, Management, Pharmacy, Informatics, English Education, and English Literature; 4) the sources of information for prospective students about Universitas Sanata Dharma are connections, location, and advertisements.